A new Bayesian method for the estimation of emergency nurses’ thresholds and agreement in the context of telephone triage - Vicovaro, Michele; Mignemi, Giuseppe; Nucci, Massimo; Bolognani, Luigi; Iannattone, Sara; Bruno, Giovanni; Spoto, Andrea (Frontiers in Psychology, 2025)
IntroductionTriage is the process aimed at ensuring that patients receive a level and quality of care matching the urgency of their conditions. The present study focuses on telephone triage. We discuss the application of a new decision-making model to the task of telephone triage.MethodsThe model allows to estimate the nurse’s Belonging Threshold (BT), which quantifies the minimum level of severity of an emergency scenario that leads the nurse to activate a rescue vehicle with emergency devices. The BT can be used as an index of the possible tendency of the nurse to systematically over-or under-triage. The model also provides accurate estimations of the level of agreement between different nurses, and between the nurses and reference experts, net of the noise due to the possible differences between the nurses’ BTs.Results and discussionThe model and the related experimental procedure were applied to a sample of 21 emergency nurses at the SUEM 118 Operations Center in Venice. We discuss how the model can be useful to identify nurses who would benefit from a training to improve the consistency of their application of the protocol, as well as to identify specific emergency scenarios for which the assignment of priority codes was most problematic.